MgrB Alterations Mediate Colistin Resistance in Klebsiella pneumoniae Isolates from Iran - Haeili, Mehri; Javani, Afsaneh; Moradi, Jale; Jafari, Zeinab; Feizabadi, Mohammad M.; Babaei, Esmaeil (Frontiers in Microbiology, 2017)
Colistin is one of the last-resort therapeutic agents to combat multidrug-resistant Gram-negative bacteria (GNB) including Klebsiella pneumoniae. Although it happens rarely, resistance to colistin has been reported for several GNB. A total of 20 colistin resistant (col-R) and three colistin susceptible (col-S) clinical isolates of K. pneumoniae were studied to explore the underlying mechanisms of colistin resistance. The presence of plasmid encoded resistance genes, mcr-1, mcr-2, mcr-3 and mcr-4 genes were examined by PCR. The nucleotide sequences of pmrA, pmrB, phoP, phoQ and mgrB genes were determined. To evaluate the association between colistin resistance and upregulation of pmrHFIJKLM and pmrCAB operons, transcriptional level of the pmrK and pmrC genes encoding for lipopolysaccharide target modifying enzymes was quantified by RT-qPCR analysis. None of the plasmid encoded resistance genes were detected in the studied isolates. Inactivation of MgrB due to nonsense mutations and insertion of IS elements was observed in 15 col-R isolates (75%). IS elements (IS5-like and IS1-like families) most commonly targeted the coding region and in one case the promoter region of the mgrB. Complementation with wild-type MgrB restored colistin susceptibility in isolates with altered mgrB. All col-R isolates lacked any genetic alterations in the pmrA, phoP and phoQ genes and substitutions identified in the pmrB were not found to be involved in resistance conferring determined by complementation assay. Colistin resistance linked with upregulation of pmrHFIJKLM and pmrCAB operons with the pmrK and pmrC being overexpressed in 20 and 11 col-R isolates respectively. Our results demonstrated that MgrB alterations are the major mechanisms contributing to colistin resistance in the tested K. pneumoniae isolates from Iran